2015
DOI: 10.3168/jds.2014-9085
|View full text |Cite
|
Sign up to set email alerts
|

Feed intake is related to changes in plasma nonesterified fatty acid concentration and hepatic acetyl CoA content following feeding in lactating dairy cows

Abstract: The relationship between hepatic acetyl CoA (AcCoA) content and dry matter intake (DMI) was evaluated using 28 multiparous Holstein cows; 14 were early postpartum (PP; 12.6 ± 3.8 d in milk) and 14 were late-lactation cows (LL; 269 ± 30 d in milk). Cows were fed once daily, and DMI was determined for the first 4h after feeding. Liver and blood samples were collected before feeding and 4h after feeding. Feed intake over the 4-h period ranged from 3.7 to 9.6 kg of dry matter and was similar for the 2 stages of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 23 publications
6
19
0
Order By: Relevance
“…Postprandial pulses of insulin interrupt the supply of fuels to the liver by stimulating the uptake of fuels by insulinsensitive tissues and inhibiting lipolysis in adipose issue. Consistent with this, feed intake over the first 4 h following feeding was highly variable among cows in the immediate postpartum period ranging from 3.7 to 9.6 kg and was positively related to the postprandial reduction of plasma NEFA concentrations which varied from 244 to 1158 μEq/l (Piantoni et al, 2015). Because the change in hepatic AcCoA concentrations was positively correlated with the change in plasma NEFA concentrations, the difference in DMI among cows was likely related to differences in the supply of AcCoA derived from β-oxidation of NEFA, consistent with the HOT.…”
Section: Interactions Of Diet and Physiological Statesupporting
confidence: 65%
See 2 more Smart Citations
“…Postprandial pulses of insulin interrupt the supply of fuels to the liver by stimulating the uptake of fuels by insulinsensitive tissues and inhibiting lipolysis in adipose issue. Consistent with this, feed intake over the first 4 h following feeding was highly variable among cows in the immediate postpartum period ranging from 3.7 to 9.6 kg and was positively related to the postprandial reduction of plasma NEFA concentrations which varied from 244 to 1158 μEq/l (Piantoni et al, 2015). Because the change in hepatic AcCoA concentrations was positively correlated with the change in plasma NEFA concentrations, the difference in DMI among cows was likely related to differences in the supply of AcCoA derived from β-oxidation of NEFA, consistent with the HOT.…”
Section: Interactions Of Diet and Physiological Statesupporting
confidence: 65%
“…Somatotropin concentrations gradually decline, decreasing milk yield and insulin resistance. Decreased milk production results in elevated plasma glucose and insulin concentrations, increasing the balance between lipogenesis and lipolysis, and decreasing plasma NEFA and hepatic AcCoA concentrations (Piantoni et al, 2015). Although NEFA is likely the dominant source of AcCoA for cows in the postpartum period when cows are in a lipolytic state, other fuels likely contribute to a greater extent when cows are in late lactation (Piantoni et al, 2015).…”
Section: Interactions Of Diet and Physiological Statementioning
confidence: 99%
See 1 more Smart Citation
“…Meal size and frequency were not affected by rate of PA infusion in a similar experiment in our laboratory (Bradford and Allen, 2007a) likely because cows were later in lactation (51 DIM) and in a different physiological state. Propionate was more hypophagic for cows in the PP period than later in lactation (Oba and Allen, 2003b), likely because cows in the PP period are in a lipolytic state with greater availability of acetyl CoA for entry into the TCA cycle (Piantoni et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting results of previous studies reported in the literature evaluating effects of diet starch concentration and fermentability are likely from interactions among diet starch concentration and fermentability, diet forage NDF (fNDF) concentration and duration of treatments. Propionate from ruminal fermentation of starch is a primary glucose precursor needed to restore euglycemia, but propionate can also suppress feed intake (Oba and Allen, 2003a;Bradford and Allen, 2007), especially for cows in the PP period that are in a lipolytic state (Oba and Allen, 2003a;Piantoni et al, 2015a). This suppression of feed intake has been linked to the stimulation of fuel oxidation in the liver by propionate, with hypophagic effects likely aggravated during the early PP period when cows increase mobilization of body reserves and acetyl CoA available for hepatic oxidation is increased (Oba and Allen, 2003b;Allen, 2012, 2013;Piantoni et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%